Neutron time-of-flight spectroscopy measurement using a waveform digitizer - 刘龙祥 王宏伟 马余刚 曹喜光 蔡翔舟 陈金根 张桂林 韩建龙 张国强 胡继峰 王小鹤 (Chinese physics C, 2016)
The photoneutron source （PNS, phase 1）, an electron linear accelerator （linac）-based pulsed neutron facility that uses the time-of-flight （TOF） technique, was constructed for the acquisition of nuclear data from the Thorium Molten Salt Reactor （TMSR） at the Shanghai Institute of Applied Physics （SINAP）. The neutron detector signal used for TOF calculation, with information on the pulse arrival time, pulse shape, and pulse height, was recorded by using a waveform digitizer （WFD）. By using the pulse height and pulse-shape discrimination （PSD） analysis to identify neutrons and ＂y-rays, the neutron TOF spectrum was obtained by employing a simple electronic design, and a new WFD-based DAQ system was developed and tested in this commissioning experiment. The DAQ system developed is characterized by a very high efficiency with respect to millisecond neutron TOF spectroscopy.